2017
DOI: 10.1016/j.scr.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Lung regeneration after toxic injury is improved in absence of dioxin receptor

Abstract: Recent experimental evidences from cellular systems and from mammalian and non-mammalian animal models highlight novel functions for the aryl hydrocarbon/dioxin receptor (AhR) in maintaining cell differentiation and tissue homeostasis. Notably, AhR depletion stimulates an undifferentiated and pluripotent phenotype likely associated to a mesenchymal transition in epithelial cells and to increased primary tumorigenesis and metastasis in melanoma. In this work, we have used a lung model of epithelial regeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 58 publications
5
20
0
Order By: Relevance
“…As cleavage of the early zygote takes place, central pluripotency factors increase their expression to produce totipotent cells that will proliferate and differentiate to generate a complete organism. We have first found that zygotes from AhR -/- mice have basal overexpression of well-known pluripotency factors Oct4, Nanog and Sox2 , in agreement with our previous studies showing that AhR-null mice have an increased ability to regenerate lung (Morales-Hernandez et al, 2017) and liver (Moreno-Marin et al, 2017) and a higher potential to sustain undifferentiation of human embryionic carcinoma cells (Morales-Hernandez et al, 2016). The apparent global role of AhR in controlling differentiation was also reported by its ability to regulate ovarian follicular development through piRNA-associated proteins, piRNAs and retrotransposons (Rico-Leo et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As cleavage of the early zygote takes place, central pluripotency factors increase their expression to produce totipotent cells that will proliferate and differentiate to generate a complete organism. We have first found that zygotes from AhR -/- mice have basal overexpression of well-known pluripotency factors Oct4, Nanog and Sox2 , in agreement with our previous studies showing that AhR-null mice have an increased ability to regenerate lung (Morales-Hernandez et al, 2017) and liver (Moreno-Marin et al, 2017) and a higher potential to sustain undifferentiation of human embryionic carcinoma cells (Morales-Hernandez et al, 2016). The apparent global role of AhR in controlling differentiation was also reported by its ability to regulate ovarian follicular development through piRNA-associated proteins, piRNAs and retrotransposons (Rico-Leo et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…AhR promotes cell differentiation through the inhibition of pluripotency genes. As a result, AhR deficiency originates an undifferentiated phenotype not only in cell lines but also in tissue regeneration in mice (Morales-Hernandez, Gonzalez-Rico et al 2016, Morales-Hernandez, Nacarino-Palma et al 2017, Moreno-Marin, Barrasa et al 2017). However, our knowledge about the role of AhR in embryo differentiation is still very limited, in particular with respect to the molecular intermediates that, been dependent on AhR, may be involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies also suggest that AHR signaling associated to coronavirus infection affects lung basal cells, which give rise to stem cells involved in lung repair in multiple contexts including influenza virus infection 29 31 . Of note, AHR-deficient mice show enhanced repair of the lung bronchiolar epithelium following naphthalene injury 32 , concomitant with the increase proliferation and the earlier activation of basal cells. Taken together, these findings suggest that AHR signaling associated to coronavirus infection may interfere with the activity of basal cells, contributing to the lung pathogenesis associated to SARS-CoV-1, MERS-CoV and SARS-CoV-2 infection.…”
Section: Introduction Results and Discussionmentioning
confidence: 99%
“…He found that the AHR, in that context, improves regeneration but inhibits cell differentiation. With elegant kinetic AHR knockdown experiments, he could demonstrate that the AHR is only needed at the start of re-differentiation, i.e., for the activation of stem cells [ 10 , 11 ]. The underlying mechanisms involve pluripotency factors such as the well-recognized octamer-binding transcription factor 4 (OCT-4) or the homeobox protein NANOG.…”
Section: Sessions and Presentationsmentioning
confidence: 99%